International Project Management Association Research Conference 2017 (UTS ePRESS, 2017)
Conference papers from the International Project Management Association Research Conference (IPMA), held on 2-4 November 2017 in Incheon, Republic of Korea, hosted by IPMA-Korea. This year's theme was: Projects, management and success: do we need a new understanding?